Characteristics and predictors of auto-stimulatory behavior in children with autism - Lukić, Ana; Arsic, Bojana; Gajic, Anja (International Journal of Educational Innovation and Research, 2023)
The aim of this research was to examine characteristics and predictors of auto stimulatory behavior in children with autism spectrum disorders (ASD), as well as to determine the presence of auto stimulatory behavior exhibited by children with ASD. The sample included 43 participants diagnosed with ASD. The instrument used was Behavior Problems Inventory (BPI-01, Rojahn et al., 2002), subscale for stereotyped behavior. Our results show that children with ASD from our sample have lower rates of auto stimulatory behavior, with the most common ones being repetitive body movements, arm shaking, bouncing around, running and pacing. The school type has not proven to be a predictor of auto stimulatory behaviors. However, male participants and those with low functioning ASD exhibit more auto stimulatory behaviors than females and those with high functioning ASD. The presence of auto stimulatory behaviors persists through age. Auto-stimulatory behaviors exhibited by children with ASD can be reduced or eliminated, however it is important to use evidence-based interventions with proven benefits for the child. Since stereotypy is usually automatically maintained and therefore is one of the behaviors that is often difficult to reduce, it is recommended that parents are taught on how to implement interventions in their home environment.